In the Shadow of the Carmens : Afield with a Naturalist in the Northern Mexican Mountains - McKinney, Bonnie Reynolds (Book collections on Project MUSE., 2012)
"A naturalist's chronicle of the Carmen Mountains of northern Mexico; essays and photographs reflect the region's biodiversity, natural history, resources, and conservation"--